Effectiveness Of Social Studies Education Teaching Methods In Promoting Democratic Participation Among Upper Basic Students In Zamfara State - Sule Muhammad (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study investigated the effectiveness of Social Studies teaching methods in promoting democratic participation among Upper Basic School students in Zamfara State, Nigeria. Guided by a descriptive survey design, data were collected from 349 students drawn from ten randomly selected schools across the state. A structured questionnaire, validated by experts and tested for reliability (Cronbach’s Alpha = 0.803), served as the instrument for data collection. Descriptive statistics (mean and standard deviation) and inferential statistics (one-sample t-test) were employed to analyze the data. Findings revealed that Social Studies teaching methods were generally effective in fostering democratic participation, with a cumulative mean of 2.72, above the decision benchmark of 2.50. Students identified interactive discussions, debates, and cooperative learning as the most impactful strategies for enhancing civic knowledge, tolerance, and participatory skills. However, the study also noted weaknesses in linking classroom learning to real-life civic practices, as activities such as community service, simulations, and civic projects received lower ratings. The one-sample t-test confirmed a significant difference in students’ views (t = 197.188, df = 348, p < .05), leading to the rejection of the null hypothesis. This underscores that Social Studies teaching methods play a meaningful role in cultivating democratic values among students in Zamfara State. The study concludes that while these methods are effective, their sustainability requires ongoing teacher training, integration of technology, and policy support to ensure stronger connections between classroom instruction and civic engagement.